IS 3PL Item Response Theory an appropriate model for dichotomous item analysis of the anatomy & physiology final examination - Ahmad Hishamuddin, Mokshein Siti Eshah, (Universiti Pendidikan Sultan Idris, 2016)
IS 3PL Item Response Theory an appropriate model for dichotomous item analysis of the anatomy & physiology final examination by Ahmad Hishamuddin, Mokshein Siti Eshah,